The Mental Health of Female Physicians and Nurses in Oman during the COVID-19 Pandemic - Khamis, Faryal (Oman Med J, 2020)
OBJECTIVES: We sought to assess the impact of the COVID-19 pandemic on female doctors and nurses’ mental health in Oman. METHODS: We conducted a cross-sectional, web-based survey of 402 female doctors and nurses recruited from several health facilities in Oman. We used the Generalized Anxiety Disorder (GAD-7) scale, the Perceived Stress Scale (PSS-10), the WHO-5 Well-Being Index (WHO-5), and the Sleep Quality Scale to determine the prevalence rates of anxiety, stress, well-being, and sleep quality. RESULTS: A total of 231 (57.5%) Omanis and 171 (42.5%) non-Omanis participated in this study. Of the total 402 participants, 28.4% were physicians and 71.6% were nurses. One in four (27.9%) participants reported caring for COVID-19 patients. One in four (27.9%) had moderate to severe anxiety. A higher proportion of Omanis (32.0%) had moderate to severe anxiety than non-Omanis (22.2%). Six in 10 (60.7%) scored at or above the mean on the PSS-10. Doctors and nurses who cared for COVID-19 patients reported higher levels of stress than those who did not. Almost half (45.3%) of the participants scored 50% or less on the well-being scale. A higher proportion of Omanis and those who cared for COVID-19 cases scored ≤ 50. Four in 10 (39.3%) had poor sleep quality; this was particularly prevalent among Omanis. A multiple regression analysis revealed that anxiety, stress, and well-being were significant predictors of poor sleep quality. CONCLUSIONS: The COVID-19 pandemic is having a significant effect on the mental health of health care workers in Oman. In this study, nurses, Omanis, and frontline health care workers were the most impacted by the global health crisis. Urgent psychological, social, and administrative interventions and support should be implemented to mitigate mental health risks in these groups.